THE EFFECT OF THE USE OF NUTRITION DISCS IN THE NUTRITION EDUCATION PROCESS ON MOTHER KNOWLEDGE AND THE CONSUMPTION PATTERN OF FRUIT AND VEGETABLES IN CHILDREN 5-9 YEARS OLD - Hafizah, Hafizah; Dewi, Zulfiana SKM (Poltekkes Kemenkes Semarang, 2021)
One of the problems related to eating behavior is the lack of consumption of fruits and vegetables. Consumption of fruits and vegetables with a proportion of 1-2 servings/day was 67.16%, while fruit and vegetable consumption was 3-4 servings/day a week for the age group â‰¥5 years of 5.00%. This shows that the consumption of fruits and vegetables of the people of Hulu Sungai Utara Regency is still insufficient. The purpose of this study was to determine the effect of using nutritional discs in the nutrition education process on maternal knowledge and consumption patterns of fruits and vegetables for children aged 5-9 years in Mamar Village, Hulu Sungai Utara Regency.This type of research is an experiment with a pretest-posttest control group design. The study population was all mothers who had children aged 5-9 years in Mamar Village. Sampling using simple random sampling technique as many as 32 people. The grouping of sample members into two different treatment groups, namely the first treatment group using nutritional disc media and the second the control group using leaflet media. This study began with a pre-test for both groups, namely measuring the mother's level of knowledge using a questionnaire and assessing children's fruit and vegetable consumption patterns using the semi-quantitative FFQ form. Then carried out nutrition education. The following week a post-test was carried out. Data analysis used Paired Sample T-test and Wilcoxon Sign Rank Test.Based on the results of the study, it shows that there is an increase in the average knowledge of mothers and children's consumption patterns through nutrition discs media before and after nutrition education. There was an effect of nutrition education in the intervention group on maternal knowledge, indicating that the value of Ï was 0,000. And there was an effect of nutrition education in the intervention group on children's fruit and vegetable consumption patterns, indicating the value of Ï was 0.003.It is hoped that respondents can apply the knowledge that has been obtained after giving nutrition education using nutrition disc media.